Holmium Yttrium-Aluminum-Garnet Laser Lithotripsy: An Effective Endoscopic Treatment for Bouveret’s Syndrome - Güler, Hasan Selim; Üsküdar, Oğuz (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Gler HS, skdar O. Holmium yttrium-aluminum-garnet laser lithotripsy: An effective endoscopic treatment for Bouverets syndrome. Turk J Gastroenterol. 2024;35(3):262-263.